Genetic Diversity and Ecological Evaluation of Fluorescent Pseudomonads Isolated from the Leaves and Roots of Potato Plants - Someya, Nobutaka (Japanese Society of Microbial Ecology/The Japanese Society of Soil Microbiology, 2012)
A total of 828 isolates of fluorescent pseudomonads (FPs) were obtained from the leaves (305 isolates) and roots (523 isolates) of potato plants grown in different geographical locations in Japan, and 16S rRNA gene sequences of 776 isolates were successfully determined by direct PCR sequencing. Clustering analysis (≥99% identity) identified 13 and 26 operational taxonomic units (OTUs) for leaf- and root-associated FPs, respectively, and 29 OTUs were identified in the phytosphere of potato plants. Among them, 7 and 9 OTUs showed a significantly biased distribution to the leaves and roots, respectively. Phylogenetic analysis revealed that 3 dominant OTUs for leaf-associated FPs were grouped in a cluster of leaf-associated pathogens, such as Pseudomonas cichorii and Pseudomonas viridiflava. In contrast, 4 OTUs were located in a cluster of saprophytic pseudomonads. Among them, 3 OTUs showed high similarity to Pseudomonas koreensis and Pseudomonas vancouverensis, both of which have been reported to be beneficial for biological control or plant growth promotion. These data provide key information for efficient surveying and utilization of beneficial FPs in agricultural practices.